2018
DOI: 10.1093/ofid/ofy210.2088
|View full text |Cite
|
Sign up to set email alerts
|

2435. Clinical Outcomes With Ceftolozane–Tazobactam in Patients With Multidrug-Resistant (MDR) Pseudomonas aeruginosa Bloodstream Infections: A Multi-Center Study

Abstract: BackgroundCeftolozane-tazobactam (TOL-TAZ) is a novel cephalosporin combination that is beneficial for the treatment of multidrug-resistant (MDR) Pseudomonas infections. However, little data are available on the utility of TOL-TAZ for patients with bloodstream infections (BSIs) caused by this organism.MethodsA retrospective, multicenter chart review was conducted at 11 hospitals to evaluate the utility of TOL-TAZ for MDR Pseudomonas BSIs from June 2016 to February 2018. Patients were included if they were over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…Cohort studies were the most commonly utilized study type (k = 13 retrospective cohort studies, [ 10 – 22 ] one prospective cohort study [ 23 ]), followed by case reports/series (k = 2 case reports [ 24 , 25 ], three case series [ 26 28 ], one case–control study [ 29 ]), and clinical trials (k = 2 randomized controlled trials [RCTs], [ 30 , 31 ] one single-arm trial [ 32 ]). Most studies were conducted in the US (k = 10) [ 10 , 11 , 17 20 , 26 28 , 33 ] and Spain (k = 6 15,18,21,25–27 ); three were conducted internationally [ 21 , 30 , 31 ], two in Italy [ 12 , 24 ], one in Japan [ 32 ], and one in Saudi Arabia [ 13 ]. The studies also varied with respect to clinical setting; with seven conducted in medical centers [ 15 , 18 , 20 , 22 , 26 28 ], thirteen conducted in hospitals [ 10 – 14 , 16 , 19 , 21 , 23 25 , 29 , 30 ], one conducted in multicenter health systems [ 17 ], and two conducted at unspecified clinical sites [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cohort studies were the most commonly utilized study type (k = 13 retrospective cohort studies, [ 10 – 22 ] one prospective cohort study [ 23 ]), followed by case reports/series (k = 2 case reports [ 24 , 25 ], three case series [ 26 28 ], one case–control study [ 29 ]), and clinical trials (k = 2 randomized controlled trials [RCTs], [ 30 , 31 ] one single-arm trial [ 32 ]). Most studies were conducted in the US (k = 10) [ 10 , 11 , 17 20 , 26 28 , 33 ] and Spain (k = 6 15,18,21,25–27 ); three were conducted internationally [ 21 , 30 , 31 ], two in Italy [ 12 , 24 ], one in Japan [ 32 ], and one in Saudi Arabia [ 13 ]. The studies also varied with respect to clinical setting; with seven conducted in medical centers [ 15 , 18 , 20 , 22 , 26 28 ], thirteen conducted in hospitals [ 10 – 14 , 16 , 19 , 21 , 23 25 , 29 , 30 ], one conducted in multicenter health systems [ 17 ], and two conducted at unspecified clinical sites [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample size of overall populations evaluated in the included studies ranged from one [ 13 , 14 , 19 , 22 , 24 , 25 ] to 398 [ 31 ] patients. However, six studies reported on patients with mixed infections [ 11 , 12 , 14 , 17 , 18 , 21 ]. Therefore, the sample size specific to patients with primary (n = 1 to 7 patients), secondary (n = 1 to 25 patients), and mixed or unspecified (n = 1 to 31 patients) bacteremia tended to be smaller and a subset of the overall population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations